2012
DOI: 10.1039/c2jm15549d
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing via phosphorescence quenching of doped metal–organic frameworks

Abstract: Three phosphorescent Ir and Ru complexes containing dicarboxylate functional groups have been doped into the framework of Zr 6 O 4 (OH) 4 (bpdc) 6 (UiO-67, bpdc ¼ para-biphenyldicarboxylate) to yield stable metal-organic frameworks (MOFs 1-3) which are highly porous with BET surface areas of 2568, 2292, and 1277 m 2 g À1 , respectively. The 3 MLCT phosphorescence of 1-3 can be effectively quenched by O 2 to provide an efficient method for oxygen detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 69 publications
1
65
0
Order By: Relevance
“…The introduction of monotopic ligands was proposed by the groups of Kitagawa and Behrens41,42 to modulate the size and shape of the crystallites of MOFs through competition of complexation with the polytopic ligands. More precisely, in the case of polycarboxylate Zr MOFs, the addition of a very large excess of monocarboxylic acid typically leads to an increase in the size of the crystallites, hence facilitating the structure determination,7,41,4350 although potentially leading to local defects 51,52. We therefore explored the effect of the addition of co‐ligands of various strengths [benzoic acid, terephthalic acid (H 2 bdc), salicylic acid (H 2 sal), catechol and pyrogallol] on the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of monotopic ligands was proposed by the groups of Kitagawa and Behrens41,42 to modulate the size and shape of the crystallites of MOFs through competition of complexation with the polytopic ligands. More precisely, in the case of polycarboxylate Zr MOFs, the addition of a very large excess of monocarboxylic acid typically leads to an increase in the size of the crystallites, hence facilitating the structure determination,7,41,4350 although potentially leading to local defects 51,52. We therefore explored the effect of the addition of co‐ligands of various strengths [benzoic acid, terephthalic acid (H 2 bdc), salicylic acid (H 2 sal), catechol and pyrogallol] on the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al reported that phosphorescent Ir and Ru complexes decorated with two carboxylate groups can be doped into the framework of a remarkably stable MOF [Zr 6 O 4 (OH) 4 (bpdc) 6 ] (UiO-67) to achieve high oxygen sensitivity with much reduced use of precious metal ( Figure 14 ). [ 127 ] UiO-67 consists of 12-connected Zr 6 O 4 (OH) 4 clusters linking by bpdc 2− ligands into an fcu topology network. The M(ppy) x (22bpy) 3− x (M = Ir(III) or Ru(II), x = 1, 2, 3) derived linear dicarboxylate ligands were used to partially (0.48-2.98%) replace the bpdc 2− ligands in UiO-67.…”
Section: Radical Gases (O 2 )mentioning
confidence: 99%
“…With the development of artificial photosynthetic device designed with molecular systems as individual functional components, molecular phosphors such as [Ir(ppy) 2 (bpy)] + and [Ru(bpy) 3 ] 2+ had been used to perform organic transformations driven by visible light . Cheng et al . also successfully incorporated catalytically competent Ir, Re, and Ru complexes into the framework of UiO‐67.…”
Section: Uio‐67 Derivativesmentioning
confidence: 99%